Evaluasi dan Strategi Peningkatan Kelas Kemampuan Kelompoktani Tahun 2019 (Studi di Dinas Pertanian dan Perikanan Kabupaten Ponorogo) - Evy Ediana (Universitas Islam Kadiri, 2021)
ABSTRACT The objectives of the research are to understand how the execution of apprisal of class of farmer group ability in Ponorogo Regency in 2019, to understand the problems as well as strategy to improve the class of farmer group ability. The research is qualitatively descriptive involving 32 farmer groups as sample and uses SWOT and QSPM as methode of data analysis. The result of research shows that advanced class dominates the apprisal result both in 2018 and 2019. The problems faced in improving of class of farmer group ability in Ponorogo Regency are: (1) farmer group is established only to access the government programes, (2) most of farmer member are in old age, (3) farmer group regulation are oftenly breached by farmers, (4) low education level of farmer causes the group is difficult to develop, (5) the organization structure of farmer group does not work as expected, (6) The decline in the interest of the younger generation to engage in agriculture, (7) the existence of farmer group is often used as political tools, (8) insufficent of agriculture instructor, (9) the difficulties of agriculture product to access market, (10) volume of subsidized fertilizer decreses, causes the increase of production cost. According to SWOT and QSPM analysis, it is understood that the strength-opportunity strategy (aggressive strategy) is suitable to increase the level of class of farmer group in Ponorogo Regency. The principe of mentioned strategy is to use internal strength to utilise natural resources especially those related to rice farming with strong guidence from competent agriculture instructor.Keywords: Farmer groups, Group Classes farmers, Class Improvement Strategies ABSTRAK Tujuan penilitian ini adalah untuk mengetahui bagaimana Pelaksanaan Penilaian Kelas Kemampuan Kelompoktani di Kabupaten Ponorogo tahun 2019, mengetahui permasalahan serta strategi Peningkatan Kelas Kemampuan Kelompoktani. Jenis penelitian deskriptif kualitatif, dengan jumlah sampel 32 kelompok. Teknik analisa data SWOT dan QSPM. Hasil penelitian menunjukkan bahwa kelas lanjut masih mendominasi pada penilaian baik di tahun 2018 maupun di tahun 2019. Permasalahan yang dihadapi dalam Peningkatan Kelas Kemampuan Kelompoktani di Kabupaten Ponorogo tahun 2019 adalah: (1) Poktan didirikan hanya untuk mengakses program saja, (2) Sebagian besar petani sudah tua, (3) Komitmen petani terhadap aturan Poktan sering dilanggar (4) Tingkat pendidikan anggota Poktan yang rendah menjadikan Poktan sulit berkembang (5) Kurang berfungsinya struktur organisasi Poktan, (6) Menurunnya minat generasi muda untuk berkecimpung di dunia pertanian, (7) Keberadaan Poktan seringkali menjadi alat politis, (8) Kurangnya tenaga penyuluh, (9) Produk pertanian kesulitan dalam mengakses pasar, (10) Volume pupuk bersubsidi berkurang sehingga biaya produksi tinggi. Menurut analisa SWOT dan QSPM diperoleh hasil bahwa strategi kekuatan peluang ( strategi agresif ) adalah strategi yang cocok untuk meningkatkan Kelas Kelompok Tani di Kabupaten Ponorogo. Prinsip strategi ini adalah menggunakan kekuatan internal untuk memanfaatkan peluang eksternal, yaitu dengan membentuk usaha poktan yang berbasis Sumber Daya Alam (SDA) terutama yang berkaitan dengan komoditas padi dengan dikawal ketat oleh Penyuluh Pertanian yang berkompeten. Kata Kunci: Kelompoktani, Kelas Kelompoktani, Strategi Peningkatan Kelas